Designing a physician leadership development program based on effective models of physician education. Issue 4 (October 2018) - Hopkins, Joseph; Fassiotto, Magali; Ku, Manwai Candy; Mammo, Dagem; Valantine, Hannah
Abstract : Background: Because of modern challenges in quality, safety, patient centeredness, and cost, health care is evolving to adopt leadership practices of highly effective organizations. Traditional physician training includes little focus on developing leadership skills, which necessitates further training to achieve the potential of collaborative management. Purpose: The aim of this study was to design a leadership program using established models for continuing medical education and to assess its impact on participants' knowledge, skills, attitudes, and performance. Methodology/Approach: The program, delivered over 9 months, addressed leadership topics and was designed around a framework based on how physicians learn new clinical skills, using multiple experiential learning methods, including a leadership active learning project. The program was evaluated using Kirkpatrick's assessment levels: reaction to the program, learning, changes in behavior, and results. Four cohorts are evaluated (2008–2011). Results: Reaction: The program was rated highly by participants (mean = 4.5 of 5). Learning: Significant improvements were reported in knowledge, skills, and attitudes surrounding leadership competencies. Behavior: The majority (80%–100%) of participants reported plans to use learned leadership skills in their work. Improved team leadership behaviors were shown by increased engagement of project team members. Results: All participants completed a team project during the program, adding value to the institution. Conclusion: Results support the hypothesis that learning approaches known to be effective for other types of physician education are successful when applied to leadership development training. Across all four assessment levels, the program was effective in improving leadership competencies essential to meeting the complex needs of the changing health care system. Practice implications: Developing in-house programs that fit the framework established for continuing medical education can increase physician leadership competencies and add value to health care institutions. Active learning projects provide opportunities to practice leadership skills addressing real word problems.